Strengthening Social Identity: The Role of Islamic Schools in Urban Muslim Communities - Mu’alimin; Imron Rosady (JIE (Journal of Islamic Education), 2025)
This qualitative phenomenological study examines the role of SD Ulul Albab as an Islamic school in shaping the social identity of urban Muslim communities in Jember. Data were collected through participant observation, semi-structured, and curriculum document analysis. Using Miles' interactive analysis model and triangulation validation, the findings reveal three key aspects: First, Strengthening collective identity through structured programs (Qur’an memorisation, congregational prayers, family-based activities) that foster social cohesion, consistent with Tajfel & Turner's social identity theory regarding the cognitive-evaluative-affective functions of groups; Second, the dialectic between strong religious identity preservation and adaptation challenges in pluralistic societies, demonstrating the complexity of value internalisation according to Ellemers; Third, the potential for exclusivity as a logical consequence of intensive group identity formation, as anticipated in Tajfel's concept of ingroup favouritism. While providing theoretical contributions to understanding Islamic education as a medium for urban identity construction, the single-case study limitation necessitates follow-up comparative and longitudinal research. Practically, these findings recommend an integrative educational model that maintains Islamic distinctiveness while developing multicultural competencies as a response to the challenges of Indonesia's increasingly pluralistic urban society.